Anticorrosion properties of epoxy-nanochitosan nanocomposite coating - Wonnie Ma, Iling Aema; Shafaamri, Ammar; Ramesh, Kasi; Vengadaesvaran, Balakrishnan; Ramesh, Subramaniam; Arof, Abdul Kariem (Elsevier, 2017)
Nanochitosan (NCH) was prepared to act as a nanofiller reinforcing agent that had been incorporated in a protective coating for corrosion protection using high-molecular-weight chitosan. In this study, a series of epoxy resin based nanocomposite coatings were prepared with various of NCH loading ratio and applied on mild steel substrates under ambient conditions. The surface morphology and structural characterization of the NCH and nanocomposite coatings were carried out using Field Emission Scanning Electron Microscope (FESEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Optical characterization of the nanocomposite specimens was examined by using UV–vis spectroscopy at a range of 300–800 nm in transmission mode. The thermal analysis of the nanocomposite coating was employed using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The corrosion protection performances of the nanocomposite coated mild steel substrates were comparatively studied using electrochemical impedance spectroscopy (EIS). The results showed that all the epoxy resin based nanocomposite coating containing NCH significantly increases the anticorrosion properties.